2019
DOI: 10.1111/jgh.14659
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in Egyptian patients with cirrhosis: Post‐therapeutic outcome and prognostic indicators

Abstract: Background and Aim Upper gastrointestinal bleeding (UGIB) is a serious complication of portal hypertension in cirrhotic patients. The objective of this study is to identify the risk factors for morbidity and mortality occurring after an UGIB attack. Methods A total of 1097 UGIB attacks in 690 patients with liver cirrhosis were studied. Their clinical, laboratory, and endoscopic data were reviewed. Results Mean age 53.2 ± 10.6 (20–90) years, 78% men and the main cause of liver disease was hepatitis C (94.9%). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
1
18
0
2
Order By: Relevance
“…Alternatively, analysis of patients with UGIB and liver disease revealed that variceal bleeding, either esophageal or gastric, was responsible for most of the UGIB attacks (57.7%) [19][20][21]. It has been reported that about half of cirrhotic patients will develop varices due to portal hypertension and 40% of them will have variceal bleeding [22].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, analysis of patients with UGIB and liver disease revealed that variceal bleeding, either esophageal or gastric, was responsible for most of the UGIB attacks (57.7%) [19][20][21]. It has been reported that about half of cirrhotic patients will develop varices due to portal hypertension and 40% of them will have variceal bleeding [22].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Despite improvements in management over the past decades, acute UGIB remains a common, life-threatening condition with mortality ranging from 5% to 11%. [1][2][3][4][5] In China, there are approximately one million UGIB patients admitted to hospitals each year, with an UGIB-specific death rate estimated to be between 4%-14%. [6] JOURNAL OF TRANSLATIONAL INTERNAL MEDICINE / APR-JUN 2021 / VOL 9 | ISSUE 2…”
Section: Introductionmentioning
confidence: 99%
“…Acute upper gastrointestinal bleeding (UGIB) is a common reason for seeking care in emergency departments (ED) and being admitted to acute care hospitals worldwide, with an incidence of 80–150 per 100,000 people each year. [ 1 , 2 , 3 , 4 , 5 ] Despite improvements in management over the past decades, acute UGIB remains a common, life-threatening condition with mortality ranging from 5% to 11%. [ 1 , 2 , 3 , 4 , 5 ] In China, there are approximately one million UGIB patients admitted to hospitals each year, with an UGIB-specific death rate estimated to be between 4%–14%.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Despite improvements in diagnosis and treatment methods, its annual incidence is 50–180 per 100,000 population, the overall mortality rate is around 10%, and this rate is estimated to reach 35% in the patients with comorbidities. 1 , 2 The early diagnosis of the patients at risk for the poor outcomes can be difficult to predict in emergency situations. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%